2014
DOI: 10.3727/096368914x678373
|View full text |Cite|
|
Sign up to set email alerts
|

Dryocrassin Suppresses Immunostimulatory Function of Dendritic Cells and Prolongs Skin Allograft Survival

Abstract: Dendritic cells (DCs) are the major specialized antigen-presenting cells for the development of optimal T-cell immunity. DCs can be used as pharmacological targets to monitor novel biological modifiers for the cure of harmful immune responses, such as transplantation rejection. Dryopteris crassirhizoma Nakai (Aspiadaceae) is used for traditional herbal medicine in the region of East Asia. The root of this fern plant has been listed for treating inflammatory diseases. Dryocrassin is the tetrameric phlorophenone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…For instance, Plantago asiatica and Capparis spinosa polysaccharides showed similar and superior phenotypic maturation capabilities, respectively, in comparison to LPS (Hamuti et al 2017;Huang et al 2014). As expected, non-polysaccharide plant extracts that suppress dendritic cell function similarly depress the expression of these maturation markers (Fu et al 2014;Li et al 2011Li et al , 2012a. Therefore, the evaluation of the relative influence on maturation marker expression is a useful predictor for potential DC based immunomodulatory properties of biological response modifiers before more elaborate studies are carried out.…”
Section: Phenotypic Maturationmentioning
confidence: 61%
“…For instance, Plantago asiatica and Capparis spinosa polysaccharides showed similar and superior phenotypic maturation capabilities, respectively, in comparison to LPS (Hamuti et al 2017;Huang et al 2014). As expected, non-polysaccharide plant extracts that suppress dendritic cell function similarly depress the expression of these maturation markers (Fu et al 2014;Li et al 2011Li et al , 2012a. Therefore, the evaluation of the relative influence on maturation marker expression is a useful predictor for potential DC based immunomodulatory properties of biological response modifiers before more elaborate studies are carried out.…”
Section: Phenotypic Maturationmentioning
confidence: 61%
“…Dryocrassin, the tetrameric phlorophenone component derived from Dryopteris crassirhizoma Nakai, inhibited the maturation and proinflammatory cytokine production in DCs induced by LPS, which might be due to inhibit LPS-induced activation of IκB kinase, JNK/p38 MAPK, and the translocation of NF-κB. Moreover, treatment with dryocrassin (100 μg/mouse) diminished DNFB-induced delayed-type hypersensitivity and extended skin allograft survival (Fu et al, 2014). Tetrandrine from the root of the creeper Stephania tetrandra S. Moore significantly downregulated the expression of CD80 and CD86 of DCs, increased the secretion of IL-10 and inhibited the allostimulatory activity.…”
Section: In Vivo Function Of Immunosuppressive Components or Extractsmentioning
confidence: 96%
“…Several studies have reported that the immunosuppressive components or extracts of CHM improve the skin allograft survival through inhibiting the maturation of DCs Fu et al, 2014;Xiang et al, 2009). Dryocrassin, the tetrameric phlorophenone component derived from Dryopteris crassirhizoma Nakai, inhibited the maturation and proinflammatory cytokine production in DCs induced by LPS, which might be due to inhibit LPS-induced activation of IκB kinase, JNK/p38 MAPK, and the translocation of NF-κB.…”
Section: In Vivo Function Of Immunosuppressive Components or Extractsmentioning
confidence: 98%
“…Skin graft rejection is largely driven by host alloresponsive T cells that are primed by dendritic cells (DCs) that express peptides captured from graft tissue (Fu et al, 2014). The DCs mature in the tissue after transporting the foreign peptides to their surface and then migrate to secondary lymph nodes where they activate and expand alloresponsive T cells (Jiang et al, 2004;Kubo et al, 2004;MartIn-Fontecha et al, 2003).…”
Section: Introductionmentioning
confidence: 99%